2001
DOI: 10.1046/j.1365-2958.2001.02571.x
|View full text |Cite
|
Sign up to set email alerts
|

The transfer of choline from the host to the bacterial cell surface requires glpQ in Haemophilus influenzae

Abstract: Haemophilus influenzae incorporates choline obtained from environmental sources onto its lipopolysaccharide as phosphorylcholine (ChoP). The decoration of the bacterial surface with ChoP contributes to pathogenesis by allowing for mimicry of the host. As the main reservoir for choline in the host is phosphatidylcholine, we tested whether other choline‐containing molecules associated with eukaryotic membranes could provide an alternative source of choline. H. influenzae was able to use glycerophosphorylcholine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…[3][4][5] In a rat otitis model, a GlpQ mutant required an approximately 100 fold-higher inoculum than the parental H. influenzae in order to induce otitis media after injection, strongly suggesting that GlpQ plays an important role as a virulence factor in H. influenzae. 6,7) Recently, a novel physiological role of H. influenzae GlpQ, closely related to the adherence of bacteria to human cells, was proposed. H. influenzae incorporates choline obtained from abundant pools of degradation products of the host cell membrane lipid by using GlpQ in its lipopolysaccaride as phosphorylcholine, which contributes to the pathogenesis by mimicry of the host cell membrane.…”
mentioning
confidence: 99%
“…[3][4][5] In a rat otitis model, a GlpQ mutant required an approximately 100 fold-higher inoculum than the parental H. influenzae in order to induce otitis media after injection, strongly suggesting that GlpQ plays an important role as a virulence factor in H. influenzae. 6,7) Recently, a novel physiological role of H. influenzae GlpQ, closely related to the adherence of bacteria to human cells, was proposed. H. influenzae incorporates choline obtained from abundant pools of degradation products of the host cell membrane lipid by using GlpQ in its lipopolysaccaride as phosphorylcholine, which contributes to the pathogenesis by mimicry of the host cell membrane.…”
mentioning
confidence: 99%
“…Refer to the Supplemental Methods for details and to Supplemental Table 1 for primers used in mutagenesis. Spontaneously streptomycin-resistant isolates of H. influenzae Eagan (a type b encapsulated strain) and an isogenic mutant lacking the surface phosphodiesterase GlpQ (ΔglpQ) were used as described previously (62). H. influenzae was grown to mid-log phase shaking at 37°C in brain-heart infusion (BHI) broth supplemented with 2% Fildes Enrichment (Thermo Scientific) and 2 μg/ml β-NAD (Sigma-Aldrich) (sBHI).…”
Section: Discussionmentioning
confidence: 99%
“…No direct homologs for pneumococcal Pce were apparent in H. influenzae by sequence analysis. However, previous work from our laboratory suggested that the highly conserved, surface-bound phosphodiesterase lipoprotein GlpQ (also known as protein D) bears the ability to efficiently hydrolyze ChoP from conjugated substrates (62). Previously ascribed a role in bacterial acquisition of choline from host cells, GlpQ has long been known to be important for virulence during mucosal infection, though the nature of its contribution has remained incompletely understood (63).…”
Section: Subversion Of Paf Signaling Is Conserved In Haemophilus Inflmentioning
confidence: 99%
“…Accordingly, protein D has been suggested as a candidate protein for the production of vaccines against infections, caused by H. influenzae strains due to its conserved antigenic properties, establishment on bacterial cell surface, and presence in both encapsulated and nonencapsulated strains (21)(22)(23)(24)(25)(26). Therefore, considering the characteristics of protein D and need for the design of appropriate vaccines against nonencapsulated H. influenzae strains, we aimed to propose a recombinant truncated D protein, based on 100% conserved regions among nontypeable H. influenzae (NTHi) strains.…”
Section: Introductionmentioning
confidence: 99%